Analysis of Hardness Test and Microstructure Test of R.54 Type Railway Rail with Variations in Heat Treatment Cooling Media - Oktavia, Amelia; Tabitha, Adinda Kanaya; Drajat, Bambang; Pujiyulianto, Eko (Journal of Engineering and Scientific Research, 2025)
Rail steel R.54 is a steel that is included in high carbon steel. Rail steel R.54 has a carbon element of 0.60-0.80% allowing the hardening process to be carried out with appropriate heat treatment . This type of research is an experimental laboratory study. The study aims to determine the effect of variations in cooling media on the observation of microstructure and hardness values in the hardening process of rail steel R.54. The Vickers method with a load of 500 gf is one of the important aspects in hardness testing. The results showed that the hardness value without heat treatment was 383.93 HV and the hardness value after heat treatment with three variations of cooling media, namely soapy water of 669.13 HV, 35% table salt (NaCl) of 689.14 HV, and new oil of 835.50 HV. The three cooling media can be concluded that the highest level of steel hardness is achieved in specimens that are hardened and cooled with new oil cooling media. The viscosity of new oil affects the hardness level of R-54 rail steel. The hardness level of R-54 rail steel will increase along with the increasing viscosity of the oil that is inserted into the cooling medium of R-54 rail steel after the quenching process. The results of observations of the microstructure of R-54 rail steel samples show that there is a phase change without heat treatment that is formed is ferrite and pearlite to form ferrite , austenite and martensite phases due to the heating process of austenite which is cooled rapidly in the cooling medium.